Multihop packet scheduling in WDM - Marsan, M.A (IEEE Transactions on communications)
This paper addresses the design of packet transmission schedules in photonic slotted wavelength-division multiplexing/time-division multiplexing broadcast-and-select networks with W wavelengths and N nodes. Nodes are equipped with one tunable-wavelength transmitter with nonnegligible tuning times and one fixed-wavelength receiver. A new scheduling algorithm that exploits multihop packet transfer to shorten the duration of scheduling periods is first proposed. A single-hop scheduling algorithm that performs slightly better than previous proposals is then described. A simulation-based analysis of the two algorithms shows that they jointly lead to significant improvements in both throughput and delay with respect to previous single-hop schedules